ANALISIS MANAJEMEN BISNIS SYARIAH PENGARUH TRANSAKSI BELANJA ONLINE DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUASAN KONSUMEN PADA E-COMMERCE SHOPEE (STUDI DI DESA PAMIJAHAN, DESA PASAREAN, DESA CIASIHAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR, JAWA BARAT) - Kusuma Tabriziah, Siti Ningrat; Trihantana, Rully; Suryani, Ermi (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2024)
Electronic Commerce (E-Commerce) is an example of advances in information technology, where business transactions are not carried out conventionally, which requires buyers to interact directly with sellers or the necessity to use cash. But the seller is represented by a system that serves buyers online through computer network media. This type of research is quantitative research, with a sample of 342 respondents taken from the Pasarean Village Community and Ciasihan Village Community who use Shopee e-commerce and who carry out online transactions. The data collection method was carried out by distributing questionnaires and google forms to the Pasarean Village Community and Ciasihan Village. Hypothesis testing using Partial Test (t test) and Simultaneous Test (F test). The results of this study indicate that there is a partial effect of online shopping transactions on consumer satisfaction, there is a partial effect of consumer trust on consumer satisfaction, and there is a simultaneous effect of online shopping transactions and consumer trust on consumer satisfaction.